Strength training under hypoxic conditions - Alvarez-Herms, J.; Julia-Sanchez, S.; Hamlin, M.; Viscor, G. (Physiological Reports, 2015)
Recently, Kon et al. (2014) published in this journal an interesting paper entitled "Effects of systemic hypoxia on human muscular adaptations to resistance exercise train-ing " which determined the effect of 8 weeks of resistance training (5 sets of 10 reps at 70% of 1 RM of free weight bench-press and bilateral leg-press using a weight-stack machine) under hypoxia (HRT, 14.4% O2) or normoxia, on muscle cross-sectorial area, 1 RM, muscular endurance and markers of mitochondrial biogenesis and angiogene-sis. Their conclusion suggested two important findings: (1) an increased muscular endurance and, (2) the promo-tion of angiogenesis in skeletal muscle in the hypoxic-trained subjects compared to the normoxic-trained sub-jects. However, in our opinion, a number of the com-ments in the Kon et al. (2014) publication need clarification, moreover, the author`s conclusions may only partially explain the benefits of resistance training in hypoxia for endurance athletes.